Na/K Pump-Induced [Na](i) Gradients in Rat Ventricular Myocytes Measured with Two-Photon Microscopy - Despa, Sanda (Biophysical Society, 2004)
Via the Na/Ca and Na/H exchange, intracellular Na concentration ([Na](i)) is important in regulating cardiac Ca and contractility. Functional data suggest that [Na](i) might be heterogeneous in myocytes that are not in steady state, but little direct spatial information is available. Here we used two-photon microscopy of SBFI to spatially resolve [Na](i) in rat ventricular myocytes. In vivo calibration yielded an apparent K(d) of 27 ± 2 mM Na. Similar resting [Na](i) was found using two-photon or single-photon ratiometric measurements with SBFI (10.8 ± 0.7 vs. 11.1 ± 0.7mM). To assess longitudinal [Na](i) gradients, Na/K pumps were blocked at one end of the myocyte (locally pipette-applied K-free extracellular solution) and active in the rest of the cell. This led to a marked increase in [Na](i) at sites downstream of the pipette (where Na enters the myocyte and Na/K pumps are blocked). [Na](i) rise was smaller at upstream sites. This resulted in sustained [Na](i) gradients (up to ∼17 mM/120 μm cell length). This implies that Na diffusion in cardiac myocytes is slow with respect to trans-sarcolemmal Na transport rates, although the mechanisms responsible are unclear. A simple diffusion model indicated that such gradients require a Na diffusion coefficient of 10–12 μm(2)/s, significantly lower than in aqueous solutions.